Islam Nusantara, Digital Polarization, and Electoral Politics: Network and Discourse Dynamics on Twitter - Basit, Lutfi (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines how Islam Nusantara, a culturally rooted interpretation of Indonesian Islam, became a contested object of public discourse on Twitter during the 2019 presidential election. The study addresses the limited understanding of how religious contestation is shaped simultaneously by network structures, discursive practices, and platform mediation. Using an integrated mixed-methods design, the analysis combines social network analysis to identify patterns of interaction and polarization with critical discourse analysis to examine narrative framing across competing communities. Drawing on a dataset of 8,437 users and 23,891 interactions, the findings reveal two key empirical patterns. Discourse on Islam Nusantara is organized into highly fragmented interaction clusters, indicating strong ideological segmentation aligned with existing religious and political divisions. At the same time, a small number of structurally central actors function as bridges, enabling selective cross-community interaction through adaptive linguistic strategies. To account for these dynamics, the study introduces the Sociotechnical Islamic Discourse Network Analysis Framework (SIDNAF), which integrates network structure and discursive analysis to explain how religious meanings circulate and gain visibility within algorithmically mediated publics. The study contributes to digital religion and political communication research by demonstrating how religious discourse in electoral contexts is shaped by the combined effects of fragmentation, selective connectivity, and platform-mediated interaction rather than by ideological conflict alone.